Social Criticism and Existential Meaning in the Song Untuk Apa/Untuk Apa? by Hindia - Iskandar, Hasan Mukti; Yulianto, Hermawan (Jurnal Multidisiplin Sahombu, 2025)
Songs often serve as a medium of communication that conveys social criticism and existential reflection on contemporary society. This study aims to reveal the existential meaning and form of social critique in the lyrics of Hindia’s song “Untuk Apa/Untuk Apa?” using Charles Sanders Peirce’s semiotic approach. This research employs a qualitative descriptive method emphasizing the process of semiosis among the representamen, object, and interpretant within each verse. Data were obtained through textual analysis and observation of the song’s social context. The findings show that the song contains signs representing emotional exhaustion, identity confusion, and critique of the productivity culture that pressures young generations. Through Peirce’s triadic relation, the meaning formed is not merely an individual complaint but an existential awareness of modern life’s absurdity. In conclusion, “Untuk Apa/Untuk Apa?” functions as a cultural text voicing self-reflection and resistance against capitalist values. This study extends semiotic research in music by highlighting the existential dimension as part of contemporary social criticism.